Attitudes of Arabic teachers towards distance learning in the schools within the green line in Palestine, and the obstacles that face them during any crisis - Shayeb, Shaheen Jameel; Bsharat, Maysa Mahmoud; Saqer, Khitam Mohamed Nathan (Journal of Educational and Psychological Sciences, 2023)
The aim of the current study is to reveal the attitudes of Arabic language teachers for the elementary school in Haifa District within the green line in Palestine towards distance learning under crises. Moreover, it monitored the most important challenges they encounter during distance learning, and the impact of these various obstacles on their attitudes, positively and negatively. The study sample consisted of 5 Arabic teachers who were selected as follows: 2 male and 3 female teachers, both are elementary school teachers. This study utilized a qualitative approach using multiple case studies - a multiple case study. Semi-structured interviews were used as a tool for the study, which include open questions directed to Arabic language teachers. Accordingly, they will obtain the qualitative data necessary to answer the research questions related to their attitudes towards distance learning and the obstacles they face in such learning during the crisis. The interviews were analyzed using thematic analysis method. The results showed that there are several obstacles facing Arabic teachers during distance learning, the most important of which are technological obstacles and pedagogical obstacles. The results also indicate that there is a contradiction in the respondents' attitudes towards distance learning; some teachers had positive attitudes towards distance learning, while others believed it was negative.
Keywords: Attitudes; Distance Learning; Obstacles in distance learning; within the green line in Palestine and Teaching during Crisis